2018
DOI: 10.21276/ijcmr.2018.5.8.12
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude of Dental Practitioners Towards Composite Restorations - A Questionnaire based Survey

Abstract: Introduction: Aesthetically pleasing restorations are much desirable in current day dentistry and efforts have been made to develop a restorative material to suit the patients desires and needs. Composite resins are currently the most popular of all tooth coloured restorative materials, which completely replaced silicate cement and acrylic resin as esthetic restoarive material. The aim of our study was to know the various clinical practices and techniques related to composite resins amongst dentists in two dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Replacement of a previous composite restoration leads to loss of more tooth structure as preparation is enlarged each time which is in turn time consuming and causes pulpal damage and also increases the chances of tooth crown fracture. 4,5,7 Kallio et al also reported that repairing of old restorations leads to tooth tissue preservation, less time consuming, and more cost-effective. 17 Preservation of the tooth substance was the most common reason (23.5%) behind the decision of repair of composite restoration in the present study substantiating Kallio et al's research and the results were consistent with study performed by Yousef and Khoja.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Replacement of a previous composite restoration leads to loss of more tooth structure as preparation is enlarged each time which is in turn time consuming and causes pulpal damage and also increases the chances of tooth crown fracture. 4,5,7 Kallio et al also reported that repairing of old restorations leads to tooth tissue preservation, less time consuming, and more cost-effective. 17 Preservation of the tooth substance was the most common reason (23.5%) behind the decision of repair of composite restoration in the present study substantiating Kallio et al's research and the results were consistent with study performed by Yousef and Khoja.…”
Section: Resultsmentioning
confidence: 99%
“…3 The major drawback associated with composite resins is that they undergo polymerization shrinkage over time which further leads to discoloration, marginal deterioration, and secondary caries. 4…”
mentioning
confidence: 99%
“…(Al-negrish, 2002;yamazaki et al, 2006) Literature search reveals numerous studies assessing knowledge towards composite restorations, factors affecting postoperative sensitivity of composite restorations among dental students and practitioners. (sajad, shafia andsharma, 2018)(pani et al, 2014;Akbar, 2015;sajad, shafia and sharma, 2018) The present questionnaire study was conducted among 100 dental students to assess the knowledge and awareness about different layering techniques of composites and their post-operative sensitivity. Figure 4: Bar graph depicts association between gender and number of students.…”
Section: Resultsmentioning
confidence: 99%
“…Literature search reveals studies assessing knowledge and awareness about different layering techniques of composites and their post-operative sensitivity among dental students are still lacking. We have numerous highly cited publications on well designed clinical trials and lab studies (Govindaraju, neelakantan and Gutmann, 2017; Azeem and sureshbabu, 2018; Jenarthanan and subbarao, 2018; manohar and sharma, 2018; nandakumar and nasim, 2018; Teja, Ramesh and priya, 2018; Janani and sandhya, 2019; Khandelwal and palanivelu, 2019;malli sureshbabu et al, 2019;poorni, srinivasan and nivedhitha, 2019;Rajakeerthi and ms, 2019;Rajendran et al, 2019;Ramarao and sathyanarayanan, 2019;siddique, nivedhitha and Jacob, 2019). This has provided the right platforms for us to pursue the current study.…”
Section: Introductionmentioning
confidence: 99%
“…Aesthetic restorations are an inseparable part of modern-day dental practice [ 1 ]. Restoration with composite material, like elsewhere, is the most popular and commonly used aesthetic restorative material in India.…”
Section: Introductionmentioning
confidence: 99%